Family planning services in developing countries: an opportunity to treat asymptomatic and unrecognised genital tract infections?. Issue 6 (December 1997) - Wilkinson, D; Ndovela, N; Harrison, A; Lurie, M; Connolly, C; Sturm, A W
Abstract : OBJECTIVE: To determine the prevalence of asymptomatic and unrecognised genital tract infections among women attending a family planning clinic in rural South Africa. METHODS: 189 consecutive women had genital samples taken to diagnose infection with Neisseria gonorrhoeae, Chlamydia trachomatis, Trichomonas vaginalis, Candida albicans, Treponema pallidum, and HIV, and to diagnose bacterial vaginosis. RESULTS: Mean age was 25 years; 155 (82%) were unmarried, 156 (83%) were currently using contraception, and 41 (22%) reported having an STD treated in the preceding 12 months. Although none volunteered abnormal urogenital symptoms, 74 (39%) had at least one elicited by direct questioning. 119 women (63%) had at least one genital infection: N gonorrhoeae (eight; 4%), C trachomatis (14; 8%), T vaginalis (26; 14%), C albicans (56; 30%), active syphilis (15; 8%), HIV (44; 24%), and bacterial vaginosis (29; 15%). 49 women (26%) had multiple infections. Most infections (71; 60%) were asymptomatic. Symptomatic women failed to recognise and report their symptoms, and routine services failed to detect the infections. CONCLUSION: Prevalence of genital tract infection is high among these women, most infections are asymptomatic, and symptomatic infections are frequently not recognised. Women attending family planning clinics in such settings should be screened for syphilis and offered testing for HIV infection. Strategies to detect and treat other genital infections need to be developed.